Planting Date Affects Growth and Yield Performance of Cauliflower (Brassica oleracea var. botrytis) - Sultana, Jinat; Mannan, Md Abdul; Kamal Uddin Khan, Shamim Ahmed; Kamal, Md Mostofa (South Asian Journal of Agriculture, 2019)
A field experiment was conducted to investigate the effect of different planting time on the growth and yield of cauliflower (Brassica oleracea var. botrytis) at the Germplasm Centre of Agrotechnology Discipline, Khulna University, Khulna, from September, 2016 to March, 2017. There were four planting times included in the experiment viz., T1: 15 October, T2: 15 November, T3: 15 December, and T4: 15 January. Data were collected on plant height (cm), number of leaves per plant, leaf length and breadth (cm), curd size (cm), individual plant weight (kg) and yield (t/ha). The tallest plant (81.20 cm), maximum number of leaves (23.60), leaf length (64.40 cm), leaf breadth (24.60 cm) and also curd length (19.80 cm) and breadth (18.00 cm) were recorded from the treatment T2 (November planting). The economic (67.08 t/ha) and biological yield (87.88 t/ha) were also found to be the highest in the treatment T2 (November planting) followed by the highest benefit cost ratio (2.15). Therefore, the planting of cauliflower could be done during November in Khulna region to ensure better growth and yield with better economic return. South Asian J. Agric., 7(1&2): 25-29